2021
DOI: 10.1007/s40744-021-00343-7
|View full text |Cite
|
Sign up to set email alerts
|

The “Climb” Towards Minimal Disease Activity in Psoriatic Arthritis

Abstract: Introduction: Minimal disease activity (MDA) is a validated outcome measure in psoriatic arthritis (PsA) defining a low disease activity state with a cutoff of 5/7. The main aim of the study was to look at the MDA divided into in the seven cutoffs, analyzing the more frequently achieved domains. The relationship between MDA, PASS, PsAID, DAPSA, and the PhGA in all cutoffs was also evaluated. Methods: Cross-sectional analysis on PsA patients satisfying CASPAR criteria. An assessment of disease activity, treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
3
3
0
Order By: Relevance
“…Our findings that disease activity based on TJC, pain, and PtGA measurements often limit the achievement of composite outcomes are generally consistent with published studies identifying pain, PtGA, skin disease, and tender joints as the most common unmet criteria in patients failing to achieve MDA/VLDA treatment targets [ 16 , 26 , 27 ]. However, in contrast to other studies [ 3 , 16 , 26 ], achievement of the skin disease criterion was not a limiting factor in attaining MDA/VLDA for most patients in DISCOVER-1 and DISCOVER-2.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings that disease activity based on TJC, pain, and PtGA measurements often limit the achievement of composite outcomes are generally consistent with published studies identifying pain, PtGA, skin disease, and tender joints as the most common unmet criteria in patients failing to achieve MDA/VLDA treatment targets [ 16 , 26 , 27 ]. However, in contrast to other studies [ 3 , 16 , 26 ], achievement of the skin disease criterion was not a limiting factor in attaining MDA/VLDA for most patients in DISCOVER-1 and DISCOVER-2.…”
Section: Discussionsupporting
confidence: 90%
“…Unlike the real-world analysis of patients treated with infliximab, golimumab, or ustekinumab [ 5 ], the present study demonstrated that guselkumab-treated patients achieved minimal SJC, PASI, and enthesitis on average within 16–20 weeks, and approximately 70% of patients had achieved near remission in these domains at week 100. The identification of different trajectories of Pt Pain, PtGA, and HAQ-DI in the present analysis is consistent with previous studies demonstrating that patient-reported MDA criteria are achieved less frequently in PsA patients [ 5 , 11 ]. Furthermore, this finding is also consistent with reports showing that time to achieve low disease activity or remission in patient-reported outcomes was considerably longer compared with physician-assessed criteria, such as SJC in patients with rheumatoid arthritis [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…In a real-world analysis of patients with PsA who received infliximab, golimumab, or ustekinumab, the MDA criteria that were least likely to be achieved were Pt Pain, PtGA, and PASI [ 5 ]. Of note, criteria for patient-reported domains of MDA may be less frequently achieved [ 5 , 11 ], owing to comorbidities associated with systemic inflammatory conditions [ 12 ], including fibromyalgia and obesity, that may indirectly contribute to unmet MDA domain criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various clinical manifestations of this multifaceted syndrome [2], we found that there is an unequal distribution of some clinical features such as dactylitis, enthesitis, and psoriasis onset age. On the other side, we found that TJC, SJC, disease activity level, and even the absence of achievement of MDA differed between the two sexes, being more prevalent in females [25]. These results are in keeping with previous data, reinforcing that the management of PsA between the two sexes is still un unmet need [26].…”
Section: Discussionsupporting
confidence: 89%